2018
DOI: 10.15406/ijh.2018.02.00112
|View full text |Cite
|
Sign up to set email alerts
|

Leaf size and specific leaf area of tropical deciduous trees increase with elevation in soil moisture content

Abstract: A functional trait-based approach provides insight into the functional variations between and within tropical deciduous forests across large gradients of soil moisture content (SMC). To test this hypothesis, we selected nine forest fragment sites in the tropical deciduous forest of India, which exhibited significant variations in SMC. At all nine sites, we measured leaf area (LA) and specific leaf area (SLA) of the four deciduous tree species (viz., Buchanania cochinchinensis, Diospyros melanoxylon, Lagerstroe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The magnitude of c g estimates is also compared to those of other studies (Table 4). As shown, the range of c g retrievals from the VDA approach is comparable to those of previous studies (e.g., Bateni et al., 2014; Chaturvedi & Raghubanshi, 2018; Hoffmann et al., 2005; Li et al., 2005; Williams et al., 2017).…”
Section: Resultssupporting
confidence: 88%
“…The magnitude of c g estimates is also compared to those of other studies (Table 4). As shown, the range of c g retrievals from the VDA approach is comparable to those of previous studies (e.g., Bateni et al., 2014; Chaturvedi & Raghubanshi, 2018; Hoffmann et al., 2005; Li et al., 2005; Williams et al., 2017).…”
Section: Resultssupporting
confidence: 88%
“…Species with larger leaves thus occur in environments with more rainfall and at more northern latitudes, i.e., in more equatorial regions, as has been observed in other taxa (e.g., Givnish, 1984; Peppe et al, 2011). We hypothesised that higher aridity would select for smaller leaf sizes to limit water loss via transpiration (Poole & Miller, 1981; Thuiller et al, 2004; Wright et al, 2017; Chaturvedi & Raghubanshi, 2018). For example, in a study on the genus Leucadendron in the Cape Floristic region, Thuiller et al (2004) observed significantly smaller leaves in species in arid environments than in species in more moist habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Plants have also shown a reduced stomatal size and increased stomatal density when exposed to drought stress (Xu & Zhou, 2008), though this response is likely species-specific (Zhang et al, 2012). Further, specific leaf area (SLA, i.e., leaf area per unit of dry mass) has been found to increase with increasing soil nutrient levels (Andersen et al, 2012) and soil moisture content (Chaturvedi & Raghubanshi, 2018) in tropical forest species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moisture stress reduces the leaf area and chlorophyll content, aggravates leaf senescence, and retards overall plant biomass (Kusvuran 2012;Sharifi and Mohammadkhani 2016). Leaf area reduction causes reduced photosynthesis and negatively affects N metabolism in the plant that eventually result in yield decline (Chaturvedi and Raghubansi 2018). Plants respond to drought stress through significant overflow of different soluble osmolytes such as amino acids, phenol and proline, which can be used as potential indicators for moisture stress and were studied extensively (Mafakheri et al 2010;Anjum et al 2011;Blum 2017).…”
Section: Introductionmentioning
confidence: 99%